2016
DOI: 10.1017/s1368980016002895
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic disparities in the diet of French children and adolescents: a multidimensional issue

Abstract: This research highlights the need for specific messages to help poorly educated families adopt good eating habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 55 publications
8
25
0
1
Order By: Relevance
“…Nevertheless, in the 271 fourth study, the highest intake category was associated with higher parental education for boys, 272 after adjustment for sex-and age-recommended amounts of vegetables (49) . In addition, these four 273 studies all showed higher fruit intake and daily consumption when parental education was higher 274 (49,(54)(55)(56) . Moreover, studies of lower quality showed positive associations between parental 275 education and fruit and vegetable consumption frequency (60,67) .…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, in the 271 fourth study, the highest intake category was associated with higher parental education for boys, 272 after adjustment for sex-and age-recommended amounts of vegetables (49) . In addition, these four 273 studies all showed higher fruit intake and daily consumption when parental education was higher 274 (49,(54)(55)(56) . Moreover, studies of lower quality showed positive associations between parental 275 education and fruit and vegetable consumption frequency (60,67) .…”
mentioning
confidence: 93%
“…The other 14 studies (17 reports) were 258 considered of lower quality (41,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74) . 260 The "vegetable" group was not defined in most reports (50,54,(56)(57)(58) ; in others (49,55) , it was composed 261 of raw, frozen, canned and cooked vegetables. The "fruit" group composition was less 262 homogeneous: some included 100% fruit juice (56) , all types of fruit juice (58) , dried fruits (56) or only 263 fresh (49) or whole fruits (57) , while some did not define composition (50,54,55) .…”
mentioning
confidence: 99%
See 3 more Smart Citations